Accumulation of Marine Debris in Seagrass Meadows in The Waters of Hiri and Mare Islands, North Maluku (Agrikan Jurnal Agribisnis Perikanan, 2024)
Marine debris have become a serious problem due to the lack of waste management from anthropogenic activities. The seagrass ecosystem has become an area for marine debris accumulation that can disrupt the bio-ecological function. This study aims at determining the sizes and weight of marine debris, quantify their densities, and examining the relationship between seagrass density and marine debris abundance. The study was conducted in September– October 2022 in the waters of Hiri and Mare Island. Marine debris data collection was carried out in observation plot (100mx50m). Seagrass data was taken on the same plot using the linear quadratic transect method. The results of the study obtained five types of marine debris, namely plastic, metal, glass, rubber, and others. The highest total amount of marine debris was found on Mare Island (208–368 items) compared to Hiri Island (58 items). Plastic was the most dominant type of marine debris (80.72%–85.97%) while glass was the lowest (0–2.47%). Macro debris were the most commonly found on both islands. The highest total weight of marine debris was found on Mare Island (4952.26–9349.98 grams), while the lowest one on Hiri Island (1129.06 grams). The abundance and accumulation of marine debris were higher on Mare Island (0.0368 gr/m2 and 0.935 gr/m2) compared to Hiri Island (0.0058 items/m2 and 0.0013 gr/m2). The highest seagrass density was found on Hiri Island (82.78 ind/m2) and the lowest on Mare Island (20.17 ind/m2). The strong relationship between seagrass and marine debris (r=0.77) on the negative way.
Keywords: Marine debris; Seagrass beds; Small island; North Maluku